Bending Waveguide Modeling For Light Trapping Into Optical Fiber - Ismail, Mohd Muzafar; Othman, Mohd Azlishah; Zakaria, Zahriladha; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Ramlee, Ridza Azri; Meor Said, Maizatul Alice; Abas, Norafizah; Zainuddin, Muhammad Noorazlan Shah; Abdul Rahim, Razilah; Mohamed Aminuddin, Mai Mariam; Idris, Muhammad Idzdihar (American Scientific Publishers, 2014)
-